Casting coating capable of improving surface smoothness of casting and preparation method thereof
By using a specific composition of refractory aggregate and suspension agent, combined with surfactant and binder, a cast coating that can significantly improve the surface finish of the casting and enhance wear resistance, suspension and adhesion, solve the problem of poor finish and performance of existing casting coatings.
Patent Information
- Application Number
- CN202411643884.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
Existing casting coatings cannot effectively improve the surface finish of castings, and their wear resistance, suspension and adhesion are poor.
The casting coating prepared by stirring is used to combine refractory aggregates composed of zircon powder, corundum powder and dysprosium oxide, combined with lithium-based bentonite and 3-methacryloyldopamine, as well as octylphenol polyoxyethylene ether as surfactant, polyvinyl alcohol and furan resin, a carrier liquid composed of water and ethylene glycol monomethyl ether, and polyether modified silicone oil as defoaming agent.
显著提高了铸件表面光洁度,并且增强了铸造涂料的耐磨性、悬浮性和附着性。
Abstract
Description
Technical Field
[0001] The invention relates to a casting coating, in particular to a casting coating capable of improving the surface finish of a casting and a preparation method thereof. Background Art
[0002] Casting coatings refer to casting auxiliary materials with specific functions that are used to coat the surface of the mold cavity and sand core during the casting process to isolate the molten metal. With the advancement of technology and the development of production, people's requirements for the quality of castings are getting higher and higher, especially the appearance quality of castings is increasingly concerned by the casting industry and casting application companies. Due to the close relationship with the quality of castings, especially the surface quality of castings, the application of casting coatings is becoming more and more extensive. Casting coatings are generally composed of raw materials such as refractory fillers, liquid carriers, binders, suspension stabilizers, and other additives. Usually, casting coatings are required to have good functionality, such as preventing sand from sticking to castings, improving the surface finish of castings, improving the refractoriness of casting surfaces, reinforcing sand mold surfaces, shielding or isolating, etc.
[0003] The invention with application number CN202011299851.2 discloses "a method for preparing a high-strength casting coating", comprising the following steps: (1) preparing a refractory composite material: mixing vermiculite powder and slag together, then calcining at 500°C for 40 minutes, then naturally cooling to room temperature, and then impregnating with sodium alkylbenzene sulfonate solution for 1.5 hours, ultrasonically treating for 10 minutes, filtering, drying to constant weight, and obtaining a calcined composite material; (2) adding polyvinyl alcohol and sodium silicate solution to a mixer in turn, stirring at a speed of 500r / min for 1 hour to obtain a binder; (3) adding the calcined composite material and the binder to a mixer in turn, stirring at a speed of 1200r / min for 40 minutes, and obtaining. The problem with this casting coating is that it cannot improve the surface finish of the casting well, and its wear resistance, suspension and adhesion are poor. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a casting coating which can improve the surface finish of a casting, and which can well improve the surface finish of a casting and has good wear resistance, suspension and adhesion.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A casting coating capable of improving the surface finish of castings is prepared from the following raw materials in parts by weight: 52-56 parts of refractory aggregate, 1-1.5 parts of suspending agent, 2-3 parts of surfactant, 1.5-2.4 parts of binder, 25-30 parts of carrier liquid and 0.2-0.6 parts of defoamer.
[0007] Furthermore, the refractory aggregate of the present invention is composed of zircon powder, corundum powder and dysprosium oxide in a weight ratio of 2:1:1.
[0008] Furthermore, the suspending agent of the present invention is composed of lithium bentonite and 3-methacryloyl dopamine in a weight ratio of 4:1.
[0009] Furthermore, the surfactant of the present invention is octylphenol polyoxyethylene ether.
[0010] Furthermore, the binder of the present invention is composed of polyvinyl alcohol and furan resin in a weight ratio of 2:1.
[0011] Furthermore, the carrier liquid of the present invention is composed of water and ethylene glycol monomethyl ether in a weight ratio of 1:1.
[0012] Furthermore, the defoaming agent of the present invention is polyether-modified silicone oil.
[0013] Another technical problem to be solved by the present invention is to provide a method for preparing the casting coating capable of improving the surface finish of castings.
[0014] To solve the above technical problems, the technical solution is:
[0015] A method for preparing a casting coating capable of improving the surface finish of a casting comprises the following steps:
[0016] S1. Weigh each raw material in parts by weight, add the suspending agent, binder and carrier liquid to a container and stir for 30-50 minutes to obtain a mixture;
[0017] S2. The refractory aggregate and surfactant are added to the mixture obtained in step S1 and stirred for 1.5-2.5 hours to obtain a mixture II;
[0018] S3. Add the defoamer to the mixture obtained in step S2, and stir for 5-10 minutes to obtain a casting coating that can improve the surface finish of the casting.
[0019] Furthermore, the stirring speed in step S1 of the present invention is 600-800 rpm.
[0020] Furthermore, the stirring speed in step S2 and step S3 of the present invention is 1200-1500 rpm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1) The refractory aggregate used in the present invention is composed of zircon powder, corundum powder and dysprosium oxide. Among them, the zircon powder has good wear resistance and fire resistance, and can effectively improve the surface finish of the casting. The corundum powder has good fire resistance and heat resistance. Dysprosium oxide can further improve the wear resistance and adhesion of the casting coating.
[0023] 2) The suspending agent used in the present invention is composed of lithium bentonite and 3-methacryloyl dopamine, wherein the lithium bentonite has excellent suspension properties, so that the refractory aggregate can be well suspended in the carrier liquid, and the 3-methacryloyl dopamine can further improve the suspension properties of the casting coating, and can also effectively improve the adhesion of the casting coating. DETAILED DESCRIPTION
[0024] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention but are not intended to limit the present invention.
[0025] Example 1
[0026] The casting coating capable of improving the surface finish of castings is prepared from the following raw materials in parts by weight: 54 parts of refractory aggregate, 1.2 parts of suspending agent, 2.7 parts of octylphenol polyoxyethylene ether, 1.8 parts of binder, 27 parts of carrier liquid, and 0.5 parts of polyether modified silicone oil, wherein the refractory aggregate is composed of zircon powder, corundum powder, and dysprosium oxide in a weight ratio of 2:1:1, the suspending agent is composed of lithium bentonite and 3-methacryloyl dopamine in a weight ratio of 4:1, the binder is composed of polyvinyl alcohol and furan resin in a weight ratio of 2:1, and the carrier liquid is composed of water and ethylene glycol monomethyl ether in a weight ratio of 1:1.
[0027] The preparation method of Example 1 comprises the following steps:
[0028] S1. Weigh each raw material in parts by weight, add the suspending agent, binder and carrier liquid to a container and stir at 700rpm for 40 minutes to obtain a mixture;
[0029] S2. The refractory aggregate, octylphenol polyoxyethylene ether was added to the mixture obtained in step S1, and stirred at a speed of 1400rpm for 2 hours to obtain a mixture II;
[0030] S3. Add the polyether-modified silicone oil to the mixture obtained in step S2, and stir at 1400 rpm for 7 minutes to obtain a casting coating that can improve the surface finish of the casting.
[0031] Example 2
[0032] A casting coating capable of improving the surface finish of a casting is prepared from the following raw materials in parts by weight: 52 parts of refractory aggregate, 1 part of suspending agent, 2.5 parts of octylphenol polyoxyethylene ether, 1.5 parts of binder, 25 parts of carrier liquid, and 0.6 parts of polyether modified silicone oil, wherein the refractory aggregate is composed of zircon powder, corundum powder, and dysprosium oxide in a weight ratio of 2:1:1, the suspending agent is composed of lithium bentonite and 3-methacryloyl dopamine in a weight ratio of 4:1, the binder is composed of polyvinyl alcohol and furan resin in a weight ratio of 2:1, and the carrier liquid is composed of water and ethylene glycol monomethyl ether in a weight ratio of 1:1.
[0033] The preparation method of Example 2 comprises the following steps:
[0034] S1. Weigh each raw material in parts by weight, add the suspending agent, binder and carrier liquid to a container and stir at 600rpm for 50 minutes to obtain a mixture;
[0035] S2. The refractory aggregate, octylphenol polyoxyethylene ether was added to the mixture obtained in step S1, and stirred at a speed of 1200rpm for 2.5 hours to obtain a mixture II;
[0036] S3. Add the polyether-modified silicone oil to the mixture obtained in step S2, and stir at a speed of 1200 rpm for 10 minutes to obtain a casting coating that can improve the surface finish of the casting.
[0037] Example 3
[0038] The casting coating capable of improving the surface finish of castings is prepared from the following raw materials in parts by weight: 55 parts of refractory aggregate, 1.4 parts of suspending agent, 2 parts of octylphenol polyoxyethylene ether, 2 parts of binder, 28 parts of carrier liquid, and 0.2 parts of polyether modified silicone oil, wherein the refractory aggregate is composed of zircon powder, corundum powder, and dysprosium oxide in a weight ratio of 2:1:1, the suspending agent is composed of lithium bentonite and 3-methacryloyl dopamine in a weight ratio of 4:1, the binder is composed of polyvinyl alcohol and furan resin in a weight ratio of 2:1, and the carrier liquid is composed of water and ethylene glycol monomethyl ether in a weight ratio of 1:1.
[0039] The preparation method of Example 3 comprises the following steps:
[0040] S1. Weigh each raw material in parts by weight, add the suspending agent, binder and carrier liquid to a container and stir at 700 rpm for 45 minutes to obtain a mixture;
[0041] S2. The refractory aggregate, octylphenol polyoxyethylene ether was added to the mixture obtained in step S1, and stirred at a speed of 1300rpm for 2 hours to obtain a mixture II;
[0042] S3. Add the polyether-modified silicone oil to the mixture obtained in step S2, and stir at 1300 rpm for 8 minutes to obtain a casting coating that can improve the surface finish of the casting.
[0043] Example 4
[0044] The casting coating capable of improving the surface finish of castings is prepared from the following raw materials in parts by weight: 56 parts of refractory aggregate, 1.5 parts of suspending agent, 3 parts of octylphenol polyoxyethylene ether, 2.4 parts of binder, 30 parts of carrier liquid, and 0.4 parts of polyether modified silicone oil, wherein the refractory aggregate is composed of zircon powder, corundum powder, and dysprosium oxide in a weight ratio of 2:1:1, the suspending agent is composed of lithium bentonite and 3-methacryloyl dopamine in a weight ratio of 4:1, the binder is composed of polyvinyl alcohol and furan resin in a weight ratio of 2:1, and the carrier liquid is composed of water and ethylene glycol monomethyl ether in a weight ratio of 1:1.
[0045] The preparation method of Example 4 comprises the following steps:
[0046] S1. Weigh each raw material in parts by weight, add the suspending agent, binder and carrier liquid to a container and stir at 800rpm for 30 minutes to obtain a mixture;
[0047] S2. The refractory aggregate and octylphenol polyoxyethylene ether were added to the mixture obtained in step S1 and stirred at a speed of 1500rpm for 1.5 hours to obtain a mixture II;
[0048] S3. Add the polyether-modified silicone oil to the mixture obtained in step S2, and stir at a speed of 1500 rpm for 5 minutes to obtain a casting coating that can improve the surface finish of the casting.
[0049] Comparative Example 1
[0050] The difference from Example 1 is that the refractory aggregate is composed of corundum powder and dysprosium oxide in a weight ratio of 1:1, that is, zircon powder is not used in the refractory aggregate.
[0051] Comparative Example 2
[0052] The difference from Example 1 is that the refractory aggregate is composed of zircon powder and corundum powder in a weight ratio of 2:1, that is, the refractory aggregate does not use dysprosium oxide.
[0053] Comparative Example 3
[0054] The difference from Example 1 is that the suspending agent is lithium bentonite, that is, the suspending agent does not use 3-methacryloyl dopamine. Comparative example: Example 1 of the invention with application number CN202011299851.2.
[0055] Experimental Example 1: Casting Surface Finish Test
[0056] The casting coatings prepared in Examples 1-4, Comparative Example 1 and Reference Example were sprayed on the surface of the sand core respectively. After the casting was completed, the sand sticking on the surface of the casting was observed. The less the sand sticking, the better the surface finish of the casting. The test results are shown in Table 1:
[0057] Sand adhesion on the casting surface Example 1 No sticky sand Example 2 No sticky sand Example 3 No sticky sand Example 4 No sticky sand Comparative Example 1 A small amount of sticky sand Comparison example A small amount of sticky sand
[0058] Table 1
[0059] It can be seen from Table 1 that the casting coatings prepared in Examples 1-4 of the present invention can all improve the surface finish of the castings well, while the casting coating prepared in the comparative example cannot improve the surface finish of the castings. Part of the raw materials used in comparative example 1 are different from those in Example 1. Compared with Example 1, the surface finish of the castings in comparative example 1 is worse than that in Example 1, indicating that the zircon powder in the refractory aggregate used in the present invention is the key to improving the surface finish of the castings.
[0060] Experimental Example 2: Wear resistance test
[0061] The wear resistance values of the casting coatings prepared in Examples 1-4, Comparative Examples 1-2 and Control Example were measured respectively with reference to JBT 9226-2008 standard. The smaller the wear resistance value, the better the wear resistance. The test results are shown in Table 2:
[0062] Wear resistance value (g, 64r) Example 1 0.13 Example 2 0.20 Example 3 0.15 Example 4 0.18 Comparative Example 1 0.36 Comparative Example 2 0.39 Comparison example 0.71
[0063] Table 2
[0064] As can be seen from Table 2, the wear resistance values of Examples 1-4 of the present invention are all lower than that of the control example, indicating that the casting coating prepared by the present invention has good wear resistance. Part of the raw materials used in Comparative Examples 1 and 2 are different from those in Example 1. Compared with Example 1, the wear resistance values of Comparative Examples 1 and 2 are increased, indicating that the zircon powder and dysprosium oxide in the refractory aggregate used in the present invention can improve the wear resistance of the casting coating.
[0065] Experimental Example 3: Adhesion Test
[0066] The casting coatings prepared in Examples 1-4, Comparative Examples 2-3 and Control Example were sprayed on a cylindrical mold heated to 160° C., respectively, with a coating thickness of 0.3 mm. After the coating was dried, the cylindrical mold was placed on a coating strength tester, the rotation number was set to 10 turns, and the coating strength tester was started to measure. The adhesion was judged by measuring the weight of the coating scraped off by the coating strength tester. The larger the weight of the scraped coating, the worse the adhesion, and the smaller the weight of the scraped coating, the better the adhesion. The test results are shown in Table 3:
[0067] Scraped coating weight (g) Example 1 0.330 Example 2 0.358 Example 3 0.372 Example 4 0.346 Comparative Example 2 0.437 Comparative Example 3 0.455 Comparison example 0.719
[0068] Table 3
[0069] As can be seen from Table 3, the weight of the coating scraped off in Examples 1-4 of the present invention is less than that in the control example, indicating that the casting coating prepared by the present invention has good adhesion. Some of the raw materials used in Comparative Examples 2 and 3 are different from those in Example 1. Compared with Example 1, the weight of the coating scraped off in Comparative Examples 2 and 3 is increased, indicating that the dysprosium oxide in the refractory aggregate and the 3-methacryloyl dopamine in the suspending agent used in the present invention can improve the adhesion of the casting coating.
[0070] Experimental Example 4: Suspension Test
[0071] 100 mL of the casting coatings prepared in Examples 1-4, Comparative Example 3 and Control Example were respectively poured into a 100 mL stoppered graduated cylinder. After standing for 24 hours, the casting coatings were observed to see if stratification occurred. If no stratification occurred, the suspension rate was 100%. If stratification occurred, the suspension rate was calculated by measuring the volume of the clarified liquid at the top of the stoppered graduated cylinder. The calculation formula was:
[0072] X=(100-V) / 100×100%
[0073] Where X is the suspension rate; V is the volume of the clear liquid at the top of the stoppered measuring cylinder, in mL.
[0074] The higher the suspension rate, the better the suspension rate. The test results are shown in Table 4:
[0075] Suspension rate (%) Example 1 99.5 Example 2 99.2 Example 3 99.6 Example 4 99.3 Comparative Example 3 95.7 Comparison example 90.3
[0076] Table 4
[0077] As can be seen from Table 4, the suspension rates of Examples 1-4 of the present invention are all higher than those of the control example, indicating that the casting coating prepared by the present invention has good suspension properties. Some of the raw materials used in Comparative Example 3 are different from those in Example 1. Compared with Example 1, the suspension rate of Comparative Example 3 is reduced, indicating that the 3-methacryloyl dopamine in the suspending agent used in the present invention can effectively improve the suspension properties of the casting coating.
[0078] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A casting coating capable of improving the surface finish of a casting, characterized in that: The invention is prepared from the following raw materials in parts by weight: 52-56 parts of refractory aggregate, 1-1.5 parts of suspending agent, 2-3 parts of surfactant, 1.5-2.4 parts of binder, 25-30 parts of carrier liquid and 0.2-0.6 parts of defoaming agent.
2. The casting coating capable of improving the surface finish of castings according to claim 1, characterized in that: The refractory aggregate consists of zircon powder, corundum powder and dysprosium oxide in a weight ratio of 2:1:
1.
3. The casting coating capable of improving the surface finish of castings according to claim 1, characterized in that: The suspending agent is composed of lithium bentonite and 3-methacryloyl dopamine in a weight ratio of 4:
1.
4. The casting coating capable of improving the surface finish of castings according to claim 1, characterized in that: The surfactant is octylphenol polyoxyethylene ether.
5. The casting coating capable of improving the surface finish of castings according to claim 1, characterized in that: The binder consists of polyvinyl alcohol and furan resin in a weight ratio of 2:
1.
6. The casting coating capable of improving the surface finish of castings according to claim 1, characterized in that: The carrier liquid consists of water and ethylene glycol monomethyl ether in a weight ratio of 1:
1.
7. The casting coating capable of improving the surface finish of castings according to claim 1, characterized in that: The defoamer is polyether modified silicone oil.
8. A method for preparing a casting coating capable of improving the surface finish of a casting according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Weigh each raw material in parts by weight, add the suspending agent, binder and carrier liquid to a container and stir for 30-50 minutes to obtain a mixture; S2. The refractory aggregate and surfactant are added to the mixture obtained in step S1 and stirred for 1.5-2.5 hours to obtain a mixture II; S3. Add the defoamer to the mixture obtained in step S2, and stir for 5-10 minutes to obtain a casting coating that can improve the surface finish of the casting.
9. The method for preparing a casting coating capable of improving the surface finish of a casting according to claim 8, characterized in that: The stirring speed in step S1 is 600-800 rpm.
10. The method for preparing a casting coating capable of improving the surface finish of a casting according to claim 8, characterized in that: The stirring speed in step S2 and step S3 is 1200-1500 rpm.
Citation Information
Patent Citations
Preparation method of high-strength casting coating
CN112317681A